Transcriptome Analysis of Zygotic Induction During Conjugative Transfer of Plasmid RP4 - Miyakoshi, Masatoshi; Ohtsubo, Yoshiyuki; Nagata, Yuji; Tsuda, Masataka (Frontiers in Microbiology, 2020)
Conjugative transfer of bacterial plasmid is one of the major mechanisms of horizontal gene transfer, which is mediated by direct contact between donor and recipient cells. Gene expression of a conjugative plasmid is tightly regulated mostly by plasmid-encoded transcriptional regulators, but it remains obscure how differently plasmid genes are expressed in each cell during the conjugation event. Here, we report a comprehensive analysis of gene expression during conjugative transfer of plasmid RP4, which is transferred between isogenic strains of Pseudomonas putida KT2440 at very high frequency. To discriminate the expression changes in the donor and recipient cells, we took advantage of conjugation in the presence of rifampicin (Rif). Within 10 minutes of mating, we successfully detected transient transcription of plasmid genes in the resultant transconjugant cells. This phenomenon known as zygotic induction is likely attributed to derepression of multiple RP4-encoded repressors. Interestingly, we also observed that the traJIH operon encoding relaxase and its auxiliary proteins were upregulated specifically in the donor cells. Identification of 5’ end of the zygotically induced traJ mRNA confirmed that the transcription start site of traJ was located 24-nt upstream of the nick site in the origin of transfer (oriT) as previously reported. Since the traJ promoter is encoded on the region to be transferred first, the relaxase may be expressed in the donor cell after regeneration of the oriT-flanking region, which in itself is likely to displace the autogenous repressors around oriT. This study provides new insights into the regulation of plasmid transfer processes.